Corrosion Behavior of Ternary Zr-25Ti-5Sn Alloy Doped with Ge as Biomaterials Implant in Simulation Body Fluid Solution - Pratama, Naufal Randi; Faizal, Faizal; Prajitno, Djoko Hadi (International Journal of Mechanical Engineering Technologies and Applications, 2020)
Corrosion research of metal alloys of Zr-25Ti-5Sn and Zr-25Ti-3Sn-2Geas biomaterials has been carried out in fluid solution. Zr-25Ti-5Snalloy is a ternary metal alloy developed for hard tissue biomaterials. Zr-25Ti-5Sn and Zr-25Ti-3Sn-2Ge alloys is melted in electric arc furnace. After being melted Zr-25Ti-5Sn and Zr-25Ti-3Sn-2Ge were characterized by optical microscopy. Hardness testing was carried out by the hardness microvickers method to determine the effect of germanium addition on Zr-25Ti-5Sn alloys. Corrosion testing of ternary metal alloys Zr-25Ti-5Sn and Zr-25Ti-3Sn-2Ge was carried out by the Tafel polarization method using three electrode systems. From the results of microstructure examination with optical microscope, the microstructure found in the ternary metal alloy Zr-25Ti-5Sn and Zr-25Ti-3Sn-2Ge are parallel plates and dendritic. The hardness test results show that the addition of germanium to the Zr-25Ti-5Sn ternary alloy increased the hardness of the alloy. Corrosion test results on ternary alloy Zr-25Ti-5Sn and Zr-25Ti-3Sn-2Geindicated that corrosion resistance of Zr-25Ti-5Snincreased when no addition of Germanium to Zr-25Ti-5Snalloy.